The relationship between problematic online game usage, depression, and life satisfaction among university students - Zuhtiye Nur Yazici; Hatice Kumcagiz (Educational Process: International Journal)
Background/purpose – In this study, the relationship between problematic online game usage, and depression and life satisfaction levels of university students was examined.